A note to: A hybrid algorithm for allocating tasks, operators, and workstations in multi-manned assembly lines. (July 2019) - Lopes, Thiago Cantos; Michels, Adalberto Sato; Magatão, Leandro
Highlights: Inconsistencies in a previous paper's results are pointed out. A property presented in a previous paper is questioned. Better answers for the practical case study's data are presented for every variant. Abstract: Some results reported in a recent paper (Chen, Y., Journal of Manufacturing Systems, 42:196–209, 2017) appear to be inconsistent. A property observed in the case study reported therein seems to also be questionable. This note points such inconsistencies and questions the validity of the observed property, showing that it is more easily attributable to features of the employed algorithm, rather than to the problem's nature or instance data. This note also presents an alternative solution method which obtains solutions that dominate those reported by the recent paper and support the critiques hereby presented. These solutions are provided as supporting information.